Effectiveness of The Card Sort Method on Improving Reading Ability Initial Understanding Structure Text Indonesia Language Subject Procedures to Grade V Students of State Elementary School 060837 West Medan - Mevy Sitorus, Ruth; Sutikno; Rahmat Kartolo; Juni Arpah; Julia Rahmadani (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze the effectiveness of the Card Sort method in improving reading ability of initial understanding of procedure text structure in grade V students of State Elementary School 060837, Medan Barat District, Medan City, Academic Year 2025-2026. The formulation of the problem in this study is: